Gut Microbiota Composition Associated With Clostridium difficile-Positive Diarrhea and C. difficile Type in ICU Patients - Duan, Juping; Meng, Xiujuan; Liu, Sidi; Zhou, Pengcheng; Zeng, Cui; Fu, Chenchao; Dou, Qingya; Wu, Anhua; Li, Chunhui (Frontiers in Cellular and Infection Microbiology, 2020)
Gut microbiota composition of intensive care unit (ICU) patients suffering from Clostridium difficile-positive diarrhea (CDpD) is poorly understood. This prospective study aims to use 16S rDNA (and metagenome) sequencing to compare the microbiota composition of 58 (and 5) ICU patients with CDpD (CDpD group), 33 (and 4) ICU patients with C. difficile negative diarrhea (CDnD group) and 21 (and 5) healthy control subjects (control group), as well as CDpD patients in A+B+ (N=34; A/B: C. difficile TcdA/B), A-B+ (N=7) and A-B- (N=17) subgroups. For 16S rDNA data, OTU clustering (tool: UPARSE), taxonomic assignment (tool: RDP classifier), α-diversity and β-diversity analyses (tool: QIIME) were conducted. For metagenome data, metagenome assembly (tool: SOAPdenovo), gene calling (tools: MetaGeneMark, CD-HIT, and SoapAligner), unigene alignment (tool: DIAMOND), taxon difference analysis (tool: Metastats) and gene annotation (tool: DIAMOND) were performed. The microbial diversity of CDpD group was lower than that of CDnD and control groups. The abundances of 10 taxa (e.g. Deferribacteres, Cryptomycota, Acetothermia) in CDpD group were significantly higher than those in CDnD group. The abundances of Saccharomycetes and Clostridia were significantly lower in CDpD in comparison with control. Some taxa were significantly different between A+B+ and A-B- subgroups. CDpD might relate to the decrease of beneficial taxa (i.e. Saccharomycetes and Clostridia) and the increase of harmful taxa (e.g. Deferribacteres, Cryptomycota, Acetothermia) in gut microbiota in ICU patients. C. difficile toxin type might be slightly associated with gut microbiota composition.